The upgrading of Mykid intialization system for IRIS Corporation Berhad (IRIS) - Samsudin, Sarimah (2006)
The usage of smart card has dramatically expands over the centuries. This is due to the needs in various areas such as healthcare, communication, self identification, banking, and many more that smart card contributes. Malaysia is one of the countries that are implementing smart card as self identification for the citizens. Malaysia has started with MyKad and recently, the government introduces MyKid as identification card for kids below 12 years old. MyKid Initialization System is a system that links two ‘firmware’, which is ‘mechanical firmware’ and ‘reader firmware’ with the mechanical parts of machine that operates the smart card operating machine. The system ran on physical machine named MRR300E. Due to several upgrading to the mechanical part of the machine, the mechanical firmware has to change. Changing the mechanical firmware caused the Machine Automation Department, hereinafter called as MAD, at IRIS need to review back the previous version of the software to enable the new firmware and hardware functioning and delivered the same task as before. Also, the upgrading involved several enhancements to the software. With this new software, security features are added that enable only the maintainer can access the maintainer page. Also, the system will be auto lock from being run after certain times. This is to enable the maintainer team to trace the condition of the machine, and how the machine operated at certain period of time. The methodology used to deliver the project is V shape methodology as this is the simpler methodology compared to others. As MAD have not implement software engineering practices before, choosing V shape is a wise move to introduce software engineering documents and practices. As a result, after competing this project, the author have produced Interface Requirement (IRS), Software Requirement Specification (SRS), Software Design Description (SDD) for the upgraded software. The upgraded software is now known as MyKid version 1.6.2. Hence, this technical report provides experienced-based discussions of software development process of upgrading Mykid Initialization System.